Perception of designers of an enabling environment for dementia care in Thailand - Yanisa Niennattrakul (Department of Architecture Faculty of Engineering Universitas Indonesia, 2023)
This paper explores the perception of designers towards an enabling environment for dementia care in Thailand. The global number of people living with dementia has increased, and the number is growing in developing countries with the decline in the quality of care and the high turnover rates of formal caregivers. A dementia-friendly environment can support the challenging dementia symptoms, employing a specialised environment for quality care that is a significant therapeutic resource for supporting residents’ well-being, such as comfort, familiarity, and organised space. Thus, the salutogenic design approach becomes vital in supporting personalised narratives related to personality, lifestyles, and a decision-making process to enable the person-centred care to enrich their quality of life. The concept of salutogenic design has become a trend for people with dementia to live in small-scale and home-like care settings to enhance meaningful daily activities in familiar domestic settings. This study thematically analyses 15 semi-structured interviews of architects and therapists in Thailand about their perception towards the dementia environment and its relation towards salutogenic design and capabilities approach. Based on such analysis, an enabling environment for dementia care should balance functions and aesthetics for the positive affordances between users and the environment. Instead of perceiving design as a physical environment, the design of an enabling environment should have contextual factors of politics, urban-rural gaps, and education for the whole community.